Historical background and current situation of pharmacy education in Mongolia - Purevsuren Sodnomtseren (Wolters Kluwer Medknow Publications, 2024)
In Mongolia, the medical education system with a long history has developed with its characteristics since ancient times. Modern medical education, including pharmacy education, began to grow in 1921. Before modern pharmaceutical science developed in Mongolia, pharmacy and pharmacy education were part of Traditional Mongolian Medicine and education. Medical knowledge and experience were transferred from generation to generation through simple teaching. From the sixteenth century, Manba Datsan was established in religious temples to teach Mongolian medicine through discipleship. Modern pharmacy education in Mongolia began in 1926 with the course training of pharmacy technicians, and pharmacist training started in 1961. Pharmacy technician training with a 3-year and pharmacist training with 5-year programs oriented on patient-centered pharmaceutical care are implemented in Mongolia. Pharmacy technicians can also study towards a B. degree in Pharmacy with an additional 3 years of training. As of 2023, seven state-owned and private higher education institutions offer pharmacy education and the number of institutions and students of pharmacy is expected to increase. The pharmacy education policy and the license examination type may be reformable, and the curricula should be regularly updated in line with international trends.